2011
DOI: 10.1097/hcm.0b013e3182078ae2
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening Affective Organizational Commitment

Abstract: This study investigates the relationship between cynicism, the perceived fairness of change management and personnel practices, and affective organizational commitment. High levels of affective organizational commitment have been shown to reduce voluntary turnover in the nursing workforce. Previous research suggests that "unfair" management practices and employee cynicism lead to lower commitment. It is not clear, however, whether the perceived fairness of particular practices influences affective commitment b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 18 publications
1
11
0
1
Order By: Relevance
“…21 Because nurses have transferable skills, it is logical that continuance commitment does not play a significant role in the models. Our findings mirror results from other work settings: outside of healthcare, several studies have shown that high OCy is related to low organizational commitment; 7,9,22 one study found that cynicism predicts 45% of the variability in organizational commitment. 8 …”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…21 Because nurses have transferable skills, it is logical that continuance commitment does not play a significant role in the models. Our findings mirror results from other work settings: outside of healthcare, several studies have shown that high OCy is related to low organizational commitment; 7,9,22 one study found that cynicism predicts 45% of the variability in organizational commitment. 8 …”
Section: Discussionsupporting
confidence: 87%
“…English and Chalon (2011) studied 1,104 registered nurses in Western Australia and found that high OCy was associated with lower levels of work commitment. 9 Leiter and Maslach (2009) studied the relationship between burnout and intent to turnover in a sample of 667 Canadian nurses. They operationalized burnout along three continuums: exhaustion-energy, cynicism-involvement and inefficacy-efficacy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean organizational commitment score of 4.6 indicated moderate organizational commitment for the participants. Organizational commitment at moderate levels reflects the uncertainty of job status, work overload, and feeling of unappreciation (English & Chalon, 2011;Liou & Cheng, 2010). A moderate level of organizational commitment can indirectly affect the financial success or failure of an institution and the quality of patient care (Idel et al, 2003;Meyer et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The general attitude of the nurses towards organisational change, despite these problems and inconveniences, has been moderate, but their attitude towards change is not as positive as would be desired because their score indicates slightly below the average. Besides, when the ATCS subdimensions are analysed, nurses got the highest score from re- For a successful change process, special attention needs to be paid to personnel management (Kuokkanen et al, 2007), fairness needs to be ensured in change and personnel practices (English & Chalon, 2011), and there should be awareness that cynicism may increase due to the increasing workload and stress brought by change (Nguyen et al, 2018). When cynicism is reduced or eliminated in organisations, the commitment and participation of employees to the organisation increase (Grama & Todericiu, 2016).…”
Section: Discussionmentioning
confidence: 99%